Growth Rate and Production of Seagrass Cymodocea rotundata in the Waters of Bontosua Island, Mattirobone Village, Liukang Tupabbiring District, Pangkep Regency - Hamsiah, Hamsiah; Asbar, Asbar; Danial, Danial; Hidayat , Irfan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
The purpose of the study was to analyze the diversity of species, growth rate and production of seagrass in the waters of Bontosua Island, Liukang Tuppabiring District, Pangkep Regency. While the specific target to be achieved is to obtain a picture of the condition of seagrass vegetation and the growth rate and production of seagrass Cymodocea rotundata in the waters of Bontosua Island, Liukang Tuppabiring District, Pangkep Regency. The method that will be used in this study is the identification of seagrass species, the method of measuring seagrass growth by marking. As supporting data, water quality measurements are carried out as a limiting factor for seagrass growth. The data obtained will be analyzed descriptively, which are arranged in the form of tables or graphs. The results obtained 9 (seven) species namely Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Cymodocea serrulata, Halophila ovalis, Halophila minor, Halodule uninervis, Halodule pinifolia and Syringodium isoetifolium. The average growth rate of C. rotundata is 8.01 mm/leaf/day while the average seagrass production is 0.047 grbk/m2/day. The physical and chemical parameters of the waters still support the growth of seagrass.